Inheriting Chinese Traditional Sports: An Integrated Model for Promoting Emei Martial Arts Development - Cheng Xing; Aman, M. S; Zainal Abidin, N.E. (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Emei Martial Arts, as a symbol of China's rich heritage, holds immense cultural significance and offers numerous health benefits. This study seeks to explore the correlation between the motivation, sense of belonging, and commitment of individuals practicing Emei martial arts. Additionally, it examines the influence of Emei Martial Arts' cultural identity as a mediator and moderator in this relationship. A stratified sampling method was employed to survey Emei Martial Arts practitioners in 40 training centres, resulting in the collection of 445 valid questionnaires. Factor analysis was conducted on the data using AMOS 26.0. The study found that motivations for practicing martial arts (enjoyment, mastery, competition/ego, physical condition, psychological condition, and appearance) had a significant positive impact on adherence to Emei Martial Arts practice (β = 0.22, t = 3.964, p < 0.001). On the other hand, there was no notable connection between affiliation and the expectations of others when it came to adhering to martial arts practice. The cultural identity of Emei Martial Arts plays a significant role in motivating individuals and ensuring their commitment to practicing martial arts (β = 0.074, p < 0.001). It also influences the connection between perceived belonging and exercise adherence (β = 0.038, p < 0.001). The perceived belonging of Emei Martial Arts practitioners had a significant positive effect on adherence (β = 0.24, t = 4.800, p < 0.001). All research hypotheses were confirmed. This study aims to enhance the research perspectives on Emei Martial Arts, thereby contributing to its preservation and promotion. Additionally, it will provide valuable insights for investigating other martial arts and traditional sports.